2017
DOI: 10.1084/jem.20161122
|View full text |Cite
|
Sign up to set email alerts
|

Blimp-1–dependent and –independent natural antibody production by B-1 and B-1–derived plasma cells

Abstract: The transcriptional regulator of B cell differentiation, Blimp-1, regulates antibody production by plasma cells after antigen stimulation. Savage et al. demonstrate that spontaneous “natural” IgM and IgG3 production is provided by a heterogeneous set of B-1–derived plasma cells and by B-1 cells; the latter neither express nor require Blimp-1 for maximal antibody production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
79
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(95 citation statements)
references
References 63 publications
(111 reference statements)
13
79
0
Order By: Relevance
“…Consistent with previous studies (reviewed in (80)), we found spontaneous IgM production to be restricted to bone marrow and spleen in both SPF-housed as well as germfree mice (81, 82). The study identified two distinct populations of natural AFC: B-1 cell-derived CD19- CD43+ IgM+ plasma cells (B-1PC) and CD19+ CD43+ IgM+ B-1 cells (82). Both cell populations contributed significantly to natural antibody production.…”
Section: B-1 Cell Regulation and Functionssupporting
confidence: 92%
See 2 more Smart Citations
“…Consistent with previous studies (reviewed in (80)), we found spontaneous IgM production to be restricted to bone marrow and spleen in both SPF-housed as well as germfree mice (81, 82). The study identified two distinct populations of natural AFC: B-1 cell-derived CD19- CD43+ IgM+ plasma cells (B-1PC) and CD19+ CD43+ IgM+ B-1 cells (82). Both cell populations contributed significantly to natural antibody production.…”
Section: B-1 Cell Regulation and Functionssupporting
confidence: 92%
“…Further analysis suggested that these B-1 cells develop into AFC without terminal differentiation (82), which is consistent with reduced but not absent serum IgM levels and normal serum levels IgG3 in mice with a B cells-specific deletion of prdm1 , the gene encoding Blimp-1 and shown to be a master regulator of B cell differentiation. The above-described effects of IL-5 on natural IgM and IgG3 may only affect the Blimp-1 dependent arm of natural antibody production, as IL-5 induces Blimp-1 expression (79), which could explain why natural IgM and IgG3 production is reduced but not gone in the absence of IL-5.…”
Section: B-1 Cell Regulation and Functionsmentioning
confidence: 54%
See 1 more Smart Citation
“…Additionally, the B1b subset generates anti-PPS Abs that contribute to adaptive immunity to systemic infection by S. pneumoniae (11, 55). Some experimental systems indicate that B1 cells can secrete Abs without adopting the canonical ASC phenotype (59), and if this transition to secreting cells does not require cell division, it might be expected to be relatively radioresistant. Hence, we also cannot rule out the possibility that a population of radioresistant B1b cells contributes to a postexposure memory response.…”
Section: Discussionmentioning
confidence: 99%
“…Natural serum IgM, like precursor B-1a cells, harbors autoreactivity, as well as cross-reactivity to bacterial polysaccharides, and it plays an important role in modulating the early immune response to infection and maintaining tissue homeostasis by opsonizing cell debris and oxidized low-density lipoprotein cholesterol for clearance (3). B-1a–derived IgM Ab-secreting cells (ASCs) with heterogeneous phenotypes have been identified in the BM and spleen (4). B-1a cells are maintained in a quiescent state in the face of chronic self-antigen stimulation, in part by constitutive expression of inhibitory coreceptors that suppress BCR signaling (58).…”
Section: Introductionmentioning
confidence: 99%